The machismo pandemic: Masculinities in times of COVID-19 - Bustillos Chinchón, Diego (2022)
This health crisis, in addition to showing the precarious health system, has shown that the machismo that prevails in Peru is as serious as this pandemic; however, it has not been given due attention. In this way, it is considered essential to perceive how this state of emergency, as a risk factor, has reinforced sexist behaviors and gender roles in Peruvian society, and, at the same time, reflect on how this should be an opportunity to question and deconstruct society. The objective of this article is to analyze the elements to reflect on the COVID-19 pandemic from the point of view of masculinity and how these can provide tools to face this situation. Likewise, face it not only in a positive way but also proactively from a future perspective in which the practices are translated into cultures where care, peace, affection and equality are central elements in the lives of men